Agriculture for Development: Toward a New Paradigm - Byerlee, Derek (2012)
The fundamental role that agriculture plays in development has long been recognized. In the seminal work on the subject, agriculture was seen as a source of contributions that helped induce industrial growth and a structural transformation of the economy. However, globalization, integrated value chains, rapid technological and institutional innovations, and environmental constraints have deeply changed the context for agriculture's role. We argue that a new paradigm is needed that recognizes agriculture's multiple functions for development in that emerging context: triggering economic growth, reducing poverty, narrowing income disparities, providing food security, and delivering environmental services. Yet, governments and donors have neglected these functions of agriculture with the result that agriculture growth has been reduced, 75% of world poverty is rural, sectoral income disparities have exploded, food insecurity has returned, and environmental degradation is widespread, compromising sustainability. Mobilizing these functions requires shifting the political economy to overcome antiagriculture policy biases, strengthening governance for agriculture, and tailoring priorities to country conditions.